Design, preparation and characterization of a 3D hierarchical auxetic lattice structure produced by selective laser melting. (October 2022) - Gao, Mu; He, Dingyong; Guo, Xingye; Wu, Hairong; Tan, Zhen; Wu, Xu; Shao, Wei; Wang, Guohong
Abstract: The three-dimensional (3D) negative Poisson's ratio auxetic structures are typically built based on a series of two-dimensional structures (2D) arrayed in 3D space according to the base vectors. In this paper, a unique lightweight 3D negative Poisson's ratio auxetic structure is proposed based on the 3D anti-tetra-chiral structure, which can be named as the auxetic contacted cube (ACC). The internal struts of this structure are connected using the hollow cubes, which reduces the stress concentration at the node connections of the contacted struts by avoiding these connections. In addition, the structure possesses the identical periodic unit-cell along all the three orientations in the Cartesian coordinate, therefore it shows the isotropic mechanical properties. The AlSi10Mg ACC specimens with different frame sizes, struts diameters, number of unit-cell, and porosity are prepared using selective laser melting (SLM) techniques. Microstructure analyses are conducted to prove the relative density and formability of the ACC specimen satisfying the preparation requirements of the SLM technology. The mechanic's performance of 27-unit-cells ACC structure with a diameter of 0.5 mm and a porosity of 89.2 % is analyzed using the finite element analysis (FEA) technology, indicating its negative Poisson's ratio, which is in good agreement with the experimental results. The impact of the building directions, the structural dimensions, the struts diameters, the unit-cell numbers, and the porosity on the mechanical performance of this ACC structure are systematically investigated.